Enhancement of alcohol aversion by the nicotinic acetylcholine receptor drug sazetidine‐A. (24th April 2020) - Touchette, Jillienne C.; Moen, Janna K.; Robinson, Jenna M.; Lee, Anna M.
Abstract: The prevalence of alcohol use disorders (AUDs) has steadily increased in the United States over the last 30 years. Alcohol acts on multiple receptor systems including the nicotinic acetylcholine receptors (nAChRs), which are known to mediate alcohol consumption and reward. We previously reported that the preclinical drug sazetidine‐A, a nAChR agonist and desensitizer, reduces alcohol consumption without affecting nicotine consumption in C57BL/6J mice. Here, we found that sazetidine‐A enhances the expression of alcohol aversion without affecting the expression or acquisition of conditioned alcohol reward in C57BL/6J mice. Microinjection of sazetidine‐A into the ventral midbrain targeting the ventral tegmental area (VTA) reduced binge alcohol consumption, implicating this region in mediating the effects of sazetidine‐A. Furthermore, the sazetidine‐A‐induced reduction in alcohol consumption was mediated by non‐α4 containing nAChRs, as sazetidine‐A reduced binge alcohol consumption in both α4 knock‐out and wild‐type mice. Finally, we found that in mice pretreated with sazetidine‐A, alcohol induced Fos transcript in Th ‐, but not Gad2 ‐expressing neurons in the VTA as measured by increased Fos transcript expression. In summary, we find that sazetidine‐A enhances the expression of alcohol aversion, which may underlie the reduction in alcohol consumption induced by sazetidine‐A. Elucidating the identity of non‐α4 nAChRs in alcohol aversion mechanisms will provide a better understanding the complex role of nAChRs in alcohol addiction and potentially reveal novel drug targets to treat AUDs. Abstract : Sazetidine‐A enhanced the expression of alcohol aversion in the conditioned place aversion test and had no effect on the expression or acquisition of conditioned alcohol reward in the conditioned place preference test in mice. Sazetidine‐A did not require the alpha4 nAChR subunit to reduce binge alcohol consumption, implicating non‐alpha4 containing nAChRs. In mice pre‐treated with sazetidine‐A, alcohol induced Fos transcript in Th‐, but not Gad2‐expressing neurons in the VTA as measured by increased Fos transcript expression.